The Effect of BDAC on Supply Chain Innovation: The Mediating Role of Learning Orientation - AFFUM DUFIE ABIGAIL (KNUST, 2023)
A Thesis submitted to the Department of Supply Chain and Information Systems, KNUST School of Business in partial fulfillment of the requirements for the degree of MASTER OF SCIENCE IN LOGISTICS AND SUPPLY CHAIN MANAGEMENT